2018
DOI: 10.5551/jat.42036
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Level among Shift and Night Workers in Japan: Cross-Sectional Analysis of the J-HOPE Study

Abstract: Aim: Shift workers have a high risk of cardiovascular disease (CVD). Systemic inflammation measured has been associated with the risk of CVD onset, in addition to classical risk factors. However, the association between work schedule and inflammatory cytokine levels remains unclear. The purpose of this study was to examine the association between work schedule and interleukin-6 (IL-6)/high-sensitivity C-reactive protein (hs-CRP) levels among Japanese workers.Methods: The present cross-sectional study was a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…We included 48 studies [ [36,[53][54][55], and 12 were unspecified [17,37,38,43,49,62,67,68,75,79,81,84]. We found significantly increased blood levels of triglycerides among permanent night shift workers (0.18; 0.03 to 0.33; p = 0.017; I 2 = 73.8%), rotating 3 × 8 shift workers (0.09; 0.03 to 0.16; p = 0.004; I 2 = 73.6%), rotating 2 × 12 shift workers (0.07; 0.01 to 0.13; p = 0.017; I 2 = 31.6%), and non-specified shift workers (0.11; 0.03 to 0.18; p = 0.004; I 2 = 80.9%) (Supplementary Data 7).…”
Section: Meta-analysis Of Triglycerides For Each Type Of Shift Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 48 studies [ [36,[53][54][55], and 12 were unspecified [17,37,38,43,49,62,67,68,75,79,81,84]. We found significantly increased blood levels of triglycerides among permanent night shift workers (0.18; 0.03 to 0.33; p = 0.017; I 2 = 73.8%), rotating 3 × 8 shift workers (0.09; 0.03 to 0.16; p = 0.004; I 2 = 73.6%), rotating 2 × 12 shift workers (0.07; 0.01 to 0.13; p = 0.017; I 2 = 31.6%), and non-specified shift workers (0.11; 0.03 to 0.18; p = 0.004; I 2 = 80.9%) (Supplementary Data 7).…”
Section: Meta-analysis Of Triglycerides For Each Type Of Shift Workmentioning
confidence: 99%
“…We included 46 studies [10,17,23,24,37,38,40,41,43,45,[47][48][49][50][51][52][53][54][55][56][57][58][59]62,[65][66][67][68][69][70][71][73][74][75][76][77][78][79][80][81][82][83][84][85][86]91]. The overall SMD was − 0.08 (95CI − 0.12 to − 0.03; p = 0.001) with an important heterogeneity (I 2 = 85.9%) ( Fig.…”
Section: Meta-analysis Of Hdl Cholesterol For Each Type Of Shift Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has also been shown that increased IL-6 levels can be found in night shift workers when compared to day shift workers, while CRP, a general marker of inflammation often measured in the clinical setting did not reveal significant differences ( 96 ). Higher IL-6 levels were also detected with sleep deprivation and fatigue ( 97 ), bullying ( 93 ), or sexual abuse ( 98 ).…”
Section: Individual-level Adversities and The Immune Systemmentioning
confidence: 99%
“…The current focus on circadian control of immune function was presaged by the observations -first published more than 50 years ago -that circulating lymphocyte counts oscillate on a daily basis in healthy humans (27) and that the susceptibility to endotoxin depends on the time of day it is administered in rodents (28). More recent work highlights epidemiological associations between night-shift work (i.e., activity and sleep patterns in opposition to the normal day-night pattern) and elevated levels of systemic inflammatory markers (29,30). Significantly, all lymphoid organs and immune cell types tested to date harbor functional clocks (31,32).…”
Section: Clocks and Immunitymentioning
confidence: 99%